ATTENUATION OF IRON OVERLOAD INDUCED LIVER TOXICITY BY HEMIDESMUS INDICUS ROOT IN SWISS ALBINO MICE - BIBHABASU HAZRA; RHITAJIT SARKAR; DIPANKAR CHAUDHURI; NIKHIL BABAN GHATE; SOURAV PANJA; NRIPENDRANATH MANDAL (International Journal of Pharma and Bio Sciences, 2015)
Iron overload in liver is associated with the oxidative damage of protein, lipid and nucleic acids which in turn manifests several human diseases. The present study was aimed to evaluate the amending effect of 70% methanol extract of Hemidesmus indicus root (HIME) on iron overload induced liver injury. Iron overload was induced by intraperitoneal administration of iron-dextran into mice. Mice administered with different doses (50, 100 and 200 mg kg-1 body weight) showed significant decrease in liver iron, serum ferritin and serum enzyme levels, along with decrease of lipid peroxidation, protein oxidation and collagen content. In addition, the extract effectively induced the antioxidant enzyme levels and also exhibited the potential activity of reductive release of ferritin iron. The ameliorating effect of HIME on damaged liver was furthermore supported by the histopathological studies that showed improved histological appearance which demonstrates HIME as a valuable traditional healer against iron induced liver toxicity.